ISLAM MITOS INDONESIA (KAJIAN ANTROPOLOGI-SOSIOLOGI) - Sardjuningsih, Sardjuningsih (IAIN PONOROGO, 2015)
The Muslims in Indonesia, they appreciate the tradition?s value so much, remarkably, the one which becomes the part of the religiousity practices and becomes one with it. Therefore, the Islamic religion manifestation in every community group is different, because of the tradition?s differences cover it; the position of tradition and the ancestors precepts which are placed equally with religion,it is toward the invisible matter or supernatural. Their exiatences are worshipped, honored, respected and even considdered cult, treated as the God in religion. Supernatural is often anthropomorphic, it means that the supernatural is often treated as the other creatures which have the ability and characters like human, animals, or plants. The community divinity concept and perception is not purely monotheism, but it is monopluralistic. Tradition which is accomodated by the in their religious practices is often connected to the myth existence in it. The myth truth is the community faith matter, emotion and mental. All of the religion processes related to doctrine, history and its development can not be separated from the existence of the myth, included religion which is claimed as the revelation religion. The myth element becomes very important in this contextual Islam, because the myth knowledge is considered as the holy story, the primordialic event about the universe genesis, the past time, and the other life. Frazer describes that the myth position in the community religion, is like the holy book in the modern religion. In every tribe and group who claim as Muslim, they have the myth practices which become the base in arrenging local Islamic practices. In the study of anthropology and sociology, the function and the role of myth, religion, and tradition can not be substancially distinguished, since everyone contains the invisible element. The myth as a story which is considered sacred as like the holy book which is able to describe the transendental primordial event. Myth is related to the traditional religion and the holy book is related to modern religion. The Sociology defines that myth is as the social stucture in creating the community condition. As a belief which is able to strengthen the community mystical side in order to be able to conserve the adhesive social values in the community.